2014
DOI: 10.3928/21650799-20140514-02
|View full text |Cite
|
Sign up to set email alerts
|

Fighting Violence Against Health Workers: A Way to Improve Quality of Care?

Abstract: Violence against health care workers impairs the quality of care. In one university medical center in France, 46% of the health care workers were physically assaulted at some point in the previous 12 months and 79% were verbally insulted. This article describes a participatory approach that was used to ensure health care workers take an active role in designing and implementing anti-violence measures. In each unit, a working group of health care professionals and managers developed an action plan for reducing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Workplace violence against healthcare providers is on the rise (Gignon et al . 2014; Yi et al . 2020), while nurses usually have the most contact with patients and face the highest risk of violent attack, such as physical and verbal violence (Gomaa et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Workplace violence against healthcare providers is on the rise (Gignon et al . 2014; Yi et al . 2020), while nurses usually have the most contact with patients and face the highest risk of violent attack, such as physical and verbal violence (Gomaa et al .…”
Section: Introductionmentioning
confidence: 99%
“…Workplace violence is a serious crisis for healthcare providers, especially nurses, all over the world (Weldehawaryat et al 2020). Workplace violence against healthcare providers is on the rise (Gignon et al 2014;Yi et al 2020), while nurses usually have the most contact with patients and face the highest risk of violent attack, such as physical and verbal violence (Gomaa et al 2015). Nurses are at risk for direct trauma exposure in their daily work consequent to workplace violence, abuse, and workplace accidents (Okoli et al 2021;Varghese et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…WPV may be underreported in most developing countries, but the aftermath effect is obvious. Although it might be difficult to estimate the cost of violence, empirical evidence suggested that WPV account for 30% of the total cost of violence to the society ( Gignon et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Workplace violence towards health workers in hospitals (Gignon et al . ; Spector et al . ) and in psychiatric/mental health units in particular (Allen ; Koukia & Zyga ) is on the rise.…”
Section: Introductionmentioning
confidence: 99%